Seasonal investigation of heavy metals in marine fishes captured from the Bay of Bengal and the implications for human health risk assessment. (December 2016) - Saha, Narottam; Mollah, M.Z.I.; Alam, M.F.; Safiur Rahman, M.
Abstract: To investigate the seasonal contamination levels and to evaluate the potential human health risks, ten heavy metals (As, Cd, Co, Cr, Cu, Mn, Ni, Pb, Se, and Zn) were measured in ten different marine fish species from the Bay of Bengal during four seasons. The metal concentrations varied significantly ( p < 0.05) among the fish species with maximum and minimum accumulation of Zn (46.47 μg/g) and Cd (0.25 μg/g), respectively. The fishes captured during summer accumulated a higher amount of metals relative to other seasons, which was attributed to a higher influx of agricultural waste, sewage and sludge by heavy rainfall and floods. According to estimated daily intake (EDI), target hazard quotient (THQ), total target hazard quotient (TTHQ), and the permissible safety limits prescribed by various agencies, consumption of the examined fish species should be considered as safe for human health. However, the estimation of carcinogenic risk (CR > 10 −5 ) due to exposure to arsenic indicated that consumers remain at risk of cancer. Highlights: Ten metals in 10 fish species from the Bay of Bengal were estimated in 4 seasons. Significant interspecies variations were observed for all metals. Metal accumulation was higher during wet summer season. Consumption of fish was safe for human health. Consumers were exposed to arsenic with carcinogenic risks.